Simultaneous HPLC Determination of Lidocaine Hydrochloride and Hexachlorophene in a Suppository Product - Cece Furwanti; Kusuma Hendrajaya; Gunawan Indrayanto (MPI (Media Pharmaceutica Indonesiana), 2020)
Antihemoroid® suppository has been produced commercially by PT. Kimia Farma, Indonesia. For QC purposes, a separated densitometric method for analysis of its active ingredients, lidocaine hydrochloride and hexachlorophene, was applied. The objective of this study was obtaining more efficient analysis method of LH and HC, therefore an HPLC procedure has been developed for the determination of both compounds simultaneously. AYMC-Triart C18 column was used with a gradient mobile phase consisting of acetonitrile and phosphate buffer 0.05 M (pH 6.0). Quantitative evaluation was performed at 220 nm. Method validation was performed according to the new methods of USP 41. Result showed that the HPLC method was simple, accurate, precise, and robust. The HPLC method can be applied in simultaneous determination of LH and HC in suppositories as a QC tool in the pharmaceutical industries.